Perkebunan Kelapa Sawit Indonesia yang Berkelanjutan - Irene Ester Ronauly (Syntax Corporation Indonesia, 2024)
Palm oil, which carries relatively high saturated fat content and is resistant to oxidation, becomes raw material for various industries, including the food industry, cosmetics and others. Therefore, palm oil is one of the most important oils. Indonesia is the largest palm oil producer in the world. From macroeconomic perspective, palm oil has a very strategic role. Besides being a source of foreign exchange, palm oil is also able to stimulate the people-centred economy and open up large employment opportunities. As technology and the globalization era develop, humans are starting to realize the importance of preserving the nature and environment for the benefit of future generations. Apart from that, global warming, which affects the climate change, is considered increasingly dangerous for humans lives and biodiversity on earth. Deforestation is one of the factors that contributes to the global warming. The expansion of palm oil plantations is linked to deforestation. Thus, the issue of sustainability is started to be raised as a relevant topic. The issue of sustainability concerns three elements, namely, profit, people and planet. Not only the economic benefits, but the preservation of nature and forests, as well as the fulfilment of human rights of the palm oil plantation workers must also be considered. The global challenge, such as the rejection of Indonesian palm oil commodities which are considered unsustainable, is also another driving factor to ensure the implementation of a sustainable system in the palm oil plantation business in Indonesia. Ultimately, preserving Indonesia’s nature and forests, as well as fulfilling the human rights of its workforce, are the interests of Indonesia.